Factors in the disapproval of courses in the FIECS - Ordoñez Mercado, Alipio Francisco (2006)
The proportion of courses failed by FIECS students is studied with the purpose of facilitating decision-making in future teaching programs or reorienting educational policy in the institution. The results indicate that 77% of students fail in one or more courses and that, in addition, the variables Laboratory Service, Student age, Study material, and Parental satisfaction affect this proportion.